2002
DOI: 10.1016/s0006-3495(02)75341-1
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Control of Sphingomyelinase Activity and Surface Topography in Lipid Monolayers

Abstract: Lipid lateral organization is increasingly found to modulate membrane-bound enzymes. We followed in real time the reaction course of sphingomyelin (SM) degradation by Bacillus cereus sphingomyelinase (SMase) of lipid monolayers by epifluorescence microscopy. There is evidence that formation of ceramide (Cer), a lipid second messenger, drives structural reorganization of membrane lipids. Our results provide visual evidence that SMase activity initially alters surface topography by inducing phase separation into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
105
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(115 citation statements)
references
References 42 publications
9
105
0
1
Order By: Relevance
“…The first direct visual evidence for sphingomyelinase-induced formation of ceramide-enriched domains in sphingomyelin monolayer under precise control of the surface intermolecular packing has been provided recently (Fanani et al, 2002). Furthermore, it has been indicated that lateral enzyme-specific out-of equilibrium organization of lipid domains represents a new level of signal transduction from local (nm) to long-range (μm) scales (Hartel et al, 2005).…”
Section: Ceramide-dependent Raft Systemmentioning
confidence: 99%
“…The first direct visual evidence for sphingomyelinase-induced formation of ceramide-enriched domains in sphingomyelin monolayer under precise control of the surface intermolecular packing has been provided recently (Fanani et al, 2002). Furthermore, it has been indicated that lateral enzyme-specific out-of equilibrium organization of lipid domains represents a new level of signal transduction from local (nm) to long-range (μm) scales (Hartel et al, 2005).…”
Section: Ceramide-dependent Raft Systemmentioning
confidence: 99%
“…Cer-induced domain segregation in several lipid mixtures with glycerophospholipids (Huang et al 1996;Carrer and Maggio 1999;Veiga et al 1999;Fanani et al 2002;Hsueh et al 2002;Sot et al 2005Sot et al , 2006Carrer et al 2006) has been reported using different biophysical approaches [see Alonso (2006, 2009) for reviews]. Cers induce high-temperature melting domains in mixtures where phospholipids display low (palmitoyl-oleoyl-PC) (Hsueh et al 2002) and high (dipalmitoyl-PC or dielaidoylphosphatidylethanolamine) (Carrer and Maggio 1999;Sot et al 2005) gel-to-fluid phase transition temperatures.…”
Section: Mixtures Of Ceramides With Sphingomyelins and Glycerophosphomentioning
confidence: 99%
“…A microscopy study combining DSC, fluorescence spectroscopy, and confocal fluorescence on the interaction of egg Cer with its relative egg SM showed the segregation of detergentresistant Cer-enriched domains (Sot et al 2006). In either premixed or enzyme-generated systems with bovine brain SM [mainly stearic (18:0) and lignoceric (24:0) acyl chains], Cer induces morphologically different Cer-enriched domains, depending on how the mixture was generated (Fanani et al 2002De Tullio et al 2008). Furthermore, different types of Cer-enriched domains are enzymatically formed in the presence of cholesterol, showing high solubility in cholesterol-rich membranes (Silva et al 2009;Ale et al 2012).…”
Section: Mixtures Of Ceramides With Sphingomyelins and Glycerophosphomentioning
confidence: 99%
See 2 more Smart Citations